Packaging and storage stability studies on hotcake mix made with coconut residue flour - Garingan, Christine M. (1995)
The effects of the amount of the coconut residue flour (CRF) ( 0%, 15%, and 30% substitution of wheat flour), antioxidant (Butylated Hydroxy Toluene or BHT and lecithin) used and fat content of CRF ( 23%, 28% and 33%) on the storage stability and sorption isotherm properties of hotcake mixes were investigated. Results indicated that CRF hotcake mixes mat be stored in polyethylene plastic bags for four weeks without any detectable rancidity nor spoilage by microorganisms. The peroxide values, an indicator of the extent of oxidation a product has undergone, were below 10 mEq/kg. The sorption isotherms obtained were asymptotic to the x-axis and were increasing at relative humidities greater than or equal to 0.95 which indicated that the mixes did not readily absorb moisture and were relatively stable.